Tightening access to early retirement: Who can adapt? - Bernhard Boockmann; Martin Kroczek; Natalie Laub (Institut für Angewandte Wirtschaftsforschung (IAW), 2023)
We study heterogeneity in the effects of two pension reforms in Germany that closed pathways into early retirement: the abolition of an old-age pension scheme for women and the abolition of a pension after unemployment or part-time work. We focus on heterogeneity with respect to several occupational characteristics. Both reforms had significant effects on individual employment states, and in both cases the effects differ significantly by occupation. The positive effect on employment is smaller in occupations with higher job strain and, in case of the old-age pension for women, the effect on unemployment is larger. The effects also differ by occupational tasks, PC use and the introduction of new technologies.
Keywords: J18; J22; J26; 330; Pension reforms; effect heterogeneity; occupational demands; occupational tasks